EXPERIMENTAL STUDY OF THE DISTRIBUTION OF FAT GLOBULES IN INTER-TERRITORIAL SPACES DURING SEPARATION - E. A. Chebotaryov (Современная наука и инновации)
Research into the distribution of fractions in the inter-plate spaces has a significant impact on the fundamentals of both elementary and hydrodynamic theory of separation. The need to develop such research arose when creating the scientific and technical basis for improving the processes and technology of centrifugal separation of dispersed phases from whey.